Membangun Karakter Generasi Emas 2045 melalui Pendidikan Islam di MI Darul Huda Gedongarum - Khusna Farikhatin, Fauziatul; Inayati, Ummi; Agustina, Lina; Ikhsan, Khosip; Azis, Mohamad Abdul; Zulianto, Aris; Mufidah, Eryul (Prodi PGMI STAI Al-Akbar Surabaya, 2025)
Indonesia aspires to became a more dignified nation by 2045, known as “Indonesia Emas”. This is rooted in Islamic Education, which is crucial for building the character of the current generation, particularly at MI Darul Huda Gedungarum. The current moral decadence and the lack of Islamic education have eroded the character of the current generation. This study aims to describe how building the character of golden generation 2045 trough Islamic education at the MI Darul Huda Gedongarum who have strong characters, noble morals, and are competitive. The background of moral decadence in today's era and also the lack of Islamic education obtained has eroded the character of the current generation of the nation. The method used is a descriptive qualitative research method. Data were obtained from observations, interview optimally with the teachers, principal, books, articles, academic journals, and appropriate research results. The results of the study show that Islamic education very influential in shaping the character of golden generation of 2045 trought the religious values taught. However, the development of technology today is a challenge in it self because it greatly affects the character of the current generation. The current generation, which is expected to become the golden generation of 2045, must of course have good character. Therefore, it is very necessary todevelop the quality of Islamic education to help strengthen the character of the current generation.